The sacral chordoma margin - Radaelli, Stefano; Uhl, Matthias (European journal of surgical oncology, 2020)
Objective - Aim of the manuscript is to discuss how to improve margins in sacral chordoma. Background - Chordoma is a rare neoplasm, arising in half cases from the sacrum, with reported local failure in >50% after surgery. - Methods - A multidisciplinary meeting of the “Chordoma Global Consensus Group” was held in Milan in 2017, focusing on challenges in defining and achieving optimal margins in chordoma with respect to surgery, definitive particle radiation therapy (RT) and medical therapies. This review aims to report on the outcome of the consensus meeting and to provide a summary of the most recent evidence in this field. Possible new ways forward, including on-going international clinical studies, are discussed. - Results - En-bloc tumor-sacrum resection is the cornerstone of treatment of primary sacral chordoma, aiming to achieve negative microscopic margins. Radical definitive particle therapy seems to offer a similar outcome compared to surgery, although confirmation in comparative trials is lacking; besides there is still a certain degree of technical variability across institutions, corresponding to different fields of treatment and different tumor coverage. To address some of these questions, a prospective, randomized international study comparing surgery versus definitive high-dose RT is ongoing. Available data do not support the routine use of any medical therapy as (neo)adjuvant/cytoreductive treatment. - Conclusion - Given the significant influence of margins status on local control in patients with primary localized sacral chordoma, the clear definition of adequate margins and a standard local approach across institutions for both surgery and particle RT is vital for improving the management of these patients.